Distinction of species of the genus Persea by RAPD and ISSR DNA markers1 - Reyes-Alemán Juan Carlos; Valadez-Moctezuma, Ernestina; Simuta-Velázco Lisandro; Barrientos-Priego, Alejandro Facundo; Gallegos-Vázquez Clemente (Revista Mexicana de Ciencias Agrícolas, 2018)
With the aim of establishing a basis to differentiate part of the Persea genetic diversity, specially of the subgenus Persea maintained in the National Avocado Germplasm Repository of Mexico, eight species were studied (P. americana, P. steyermarkii, P. schiedeana, P. lingue, P. nubigena, P. floccosa,P.cinerascensyP.indica)withmolecularmarkers by means of RAPD and ISSR techniques, where the PCR products were separated in acrylamide gels. The DNA fingerprinting was analyzed with multivariate statistical methods and bootstrapping to establish their genomic relationships. Useful DNA polymorphic fragments were found for the inter and intra-specific distinction of the eight species of Persea considered in the study. The statistical analysisoftheDNAfingerprintsbymeansofRAPDgrouped the different species congruently with the actual taxonomic classification,comparedwithISSR.Accordingtothepresent study, P. indica y P. lingue show less genomic relationship with the rest of the species studied, and this is accordance to the fact that they correspond to the subgenus Eriodaphne. The results permitted to differentiate genotypes of the different species of the subgenus Persea that includes P. americana and an inter-specific hybrid included in the study.